2016
DOI: 10.3892/etm.2016.3111
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial nitric oxide synthase gene polymorphism is associated with Legg-Calvé-Perthes disease

Abstract: Abstract. The aim of this study was to assess the association of 27-bp variable number tandem repeat (VNTR) polymorphism in intron 4 and G894T polymorphism in exon 7 of the endothelial nitric oxide synthase (eNOS) gene with Legg-Calvé-Perthes disease (LCPD), and to provide a scientific basis for further research into the pathogenic mechanism. A total of 80 patients with LCPD and 100 healthy subjects were recruited in this case-control study. The 27-bp VNTR and G894T polymorphisms of the eNOS gene were genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 37 publications
1
20
1
Order By: Relevance
“…According to Najafi et al (2013), women with infertility showed a higher eNOS expression only in the uterine luminal epithelium compared to the control group. Moreover, studies reveal the increased expression of eNOS in the endometrium throughout the menstrual cycle in patients with endometriosis compared to women without endometriosis, and higher levels of NO in the ectopic endometrium compared to the eutopic endometrium (Kim et al, 2009;Seckin et al, 2016;Zhao et al, 2016). Pena et al (2000) demonstrated in his study that there is a great difficulty to obtain a genetically representative sample of the Brazilian population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Najafi et al (2013), women with infertility showed a higher eNOS expression only in the uterine luminal epithelium compared to the control group. Moreover, studies reveal the increased expression of eNOS in the endometrium throughout the menstrual cycle in patients with endometriosis compared to women without endometriosis, and higher levels of NO in the ectopic endometrium compared to the eutopic endometrium (Kim et al, 2009;Seckin et al, 2016;Zhao et al, 2016). Pena et al (2000) demonstrated in his study that there is a great difficulty to obtain a genetically representative sample of the Brazilian population.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide (NO) is a multifunctional biomolecule synthesized from L-arginine by three isoenzymes of Nitric Oxide Synthase (NOS): neuronal nitric oxide synthase (nNOS), induced nitric oxide synthase (iNOS) and endothelial nitric oxide synthase (eNOS) (Seckin et al, 2016;Zhao et al, 2016). Nitric oxide is responsible for the regulation of vasodilation, exerting its effect by regulating the migration of endothelial cells, and it takes part in several physiological processes including angiogenesis, thrombosis, coagulation and fibrinolysis (Zhao et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of eNOS G894T polymorphism was conducted by polymerase chain reaction (PCR)-restriction fragment length polymorphism method as previously described [ 15 ]. The sequences of primers used for PCR reaction were as follows, forward: 5′-AAGGCAGGAGACAGTGGATGG-3′ and reverse: 5′-CCCAGTCAATCCCTTTGGTGCT CA-3′.…”
Section: Methodsmentioning
confidence: 99%